The CD147/MMP‐2 signaling pathway may regulate early stage cardiac remodelling in spontaneously hypertensive rats. (November 2016) - Li, Bowei; Zhou, Wanxing; Yang, Xiaorong; Zhou, Yuliang; Tan, Yongjing; Yuan, Congcong; Song, Yulan; Chen, Xiao; Zhang, Wei
Summary: Previous studies have reported that decreased matrix metalloproteinase‐2 (MMP‐2) is associated with early stage (age 8–16 weeks) ventricular remodelling in spontaneously hypertensive rats (SHR). We hypothesized that inhibited CD147/MMP‐2 signalling might down‐regulate MMP‐2 expression and augment remodelling in spontaneously hypertensive rats. Twenty‐nine male SHR (8 weeks) were randomly assigned to SHR, CD147, and CD147+DOX groups. The control group included eight age‐matched WKY rats. CD147 and CD147+DOX groups received recombinant human CD147 (600 ng/kg in 1.5 mL saline, weekly). The SHR and WKY groups received the vehicle. The CD147+DOX group also received doxycycline, an inhibitor of MMPs (daily, 30 mg/kg in 1.5 mL saline, iG ). On day 56 echocardiography and left ventricular mass index (LVWI) measurements were collected and histological sections were stained for cell and collagen content. Myocardium MMP‐2, TIMP‐1, CD147, and collagens types I and III were estimated by western blot. CD147 and the ratio of MMP‐2/TIMP‐1 were lower in SHR than WKY rats ( P <.05). Myocyte hypertrophy, partial fibre breaks, plasmolysis, necrosis and collagen content (collagen volume fraction [CVF], I and III) in SHR were above control levels ( P <.05). CD147 rats showed CD147, MMP‐2 and MMP‐2/TIMP‐1 were increased ( P <.05), CVF, LVWI, and collagen I and III were decreased ( P <.05) and myocyte morphology was improved. CD147 levels did not differ between CD147+DOX and CD147 groups, CVF, collagens type I and III and partial fiber breaks were more abundant in CD147+DOX ( P <.05). In summary, an inhibited CD147/MMP‐2 pathway was associated with early stage cardiac remodelling, and CD147 supplementation may attenuate this response.